Studi Kasus Guru TK dan RA : Guru Idola Dalam Perspektif Anak - Mardliyah, Mardliyah; Formen, Ali; Pranoto, Yuli Kurniawati Sugiyo (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
The importance of children expressing their opinions, being heard, and being facilitated has a significant impact on their lives and serves as a protective factor against various risks. Freedom of speech is an important element in improving children's welfare, safety, and development. This study aims to explore children's perspectives on their ideal teacher, based on their right to express their thoughts on the definition of an ideal teacher according to them. The research used a qualitative method with a case study approach through two-cycle coding, where the first coding was done on data units and the second coding was used to validate the previous results. The research participants consisted of 39 children, 12 guardians, and two kindergarten and RA teachers in Pati Regency, with data obtained through interviews, observation, and documentation. The results showed that the two teachers from the kindergarten and RA were viewed as ideal teachers by both children and adults, with characteristics including pedagogical competence, personality, professionalism, social skills, and attractive appearance. This study contributes to broadening the understanding of children's voices regarding ideal teachers in early childhood education, which can serve as a basis for teachers to improve the quality of learning and pedagogical relationships that are more child-centered.